LAPORAN TUGAS AKHIR IDENTIFIKASI LIMBAH CAIR DI INDUSTRI TEMPE MURNI MUCHLAR BANTUL, YOGYAKARTA - , PUPUT INDAH BUDI L; , Prof. Dr. Ir. M. Maksum Mahfoedz, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tempe Murni Muchlar is one of the industries that produce tempeh. In the production process is not only the final product in the form of tempe, but also produces by products and waste. The most dominating waste is liquid waste. Industrial wastewater in Tempe Muchlar discharged directly into waters without any treatment. Wastewater treatment needed by industry to prevent any contamination of the waters and the surrounding environment. Laboratory testing is necessary to determine the pollution load indicators contained in the waste cair. Laboratory tests carried out in the Laboratory of Hydrology and Water Quality, Faculty of Geography, Gadjah Mada University. The sample used in the form of 3 samples of liquid waste soy marinade. Sampling of waste aims to determine the levels of BOD, COD, Ammonia, Nitrate, TSS, and pH. As a reference used effluent standards based Pergub DIY No. 7 Year 2010. From the test results, levels of BOD 552.17 ± 138.80 mg/L, COD 10618.97 ± 1661.06 mg/L, Ammonia 0.36 ± 0.24 mg/L, Nitrat 0,33 ± 0 , 31 mg/L, TSS 1632.93 ± 1300.03 mg/L and pH 0.02 ± 4,86 exceeds predefined quality standards. In need of appropriate wastewater treatment to reduce the value of the parameters of BOD, COD, TSS and pH.